A negative electrode additive for lead-acid battery and preparation method thereof

By using SNO2, COF, and porous nitrogen nitride nanoma composite materials as additives in the negative board of lead -acid batteries, the traditional lead -acid batteries have the problems of short circulation life and serious sulfuric acidization of traditional lead -acid batteries under the state of high magnification. The battery performance is improved.

CN119170803BActive Publication Date: 2025-01-28JIANGXI HERUNYU POWER TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411609309.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-28
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Traditional lead-acid batteries have short cycle life, low discharge capacity, easy water loss of electrolyte, overflow of acid gases, and serious sulfurization of the negative electrode plate, affecting battery performance.

Method used

Using SNO2, COF, and porous nitride nano nanoma composite materials as negative polar additives, through synthetic porous carbon nano -nanotubes, COF@porous nitride nano -nano tubes, and SNO2@cof@polymorite carbon nanotuba composite materials, add negative electrode In the board, improve the phenomenon of sulfate and increase the hydrogen analysis.

Benefits of technology

Effectively improve the circulation life of lead -acid batteries and hydrogen analysis of hydrogen analysis, reduce the precipitation of hydrogen, alleviate the water loss of electrolyte and the increase in the internal pressure of the battery, and improve the performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170803B_ABST
    Figure CN119170803B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lead-acid batteries, and discloses a negative electrode additive for lead-acid batteries and a preparation method thereof. The negative electrode additive of the present invention is a composite material obtained by compounding SnO2, COF and carbon nitride nanotubes, wherein the composite material is SnO2@COF@porous carbon nitride nanotubes, wherein the amount of the negative electrode additive added is 0.25% of the mass of the negative electrode lead powder of the lead-acid battery; the addition of SnO2@COF@porous carbon nitride nanotubes effectively improves the sulfation phenomenon of the negative electrode of the lead-acid battery, improves the high-rate partial charge state of the lead-acid battery, thereby improving the cycle life of the battery, and at the same time, also improves the hydrogen evolution overpotential of the negative electrode plate, reduces the precipitation of hydrogen, thereby effectively alleviating the dehydration of the electrolyte, the increase of the internal pressure of the battery and the impact on the electrode plate, which is conducive to maintaining the stability of the electrode plate and the battery, thereby improving the use performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lead-acid batteries, and in particular to a negative electrode additive for lead-acid batteries and a preparation method thereof. Background Art

[0002] Lead-acid batteries are widely used in various fields due to their safety, reliability, high recovery rate (recovery rate up to 99.9%), and high cost-effectiveness. They are currently the most produced type of storage battery, and my country's lead-acid battery production ranks first in the world. With the continuous development of electronic technology, batteries are required to have long cycle life and high discharge capacity under high-rate partial state of charge (HRPSoC), but traditional lead-acid batteries cannot meet such high requirements. The main disadvantages are as follows: 1) At the end of battery charging, the plates will undergo violent hydrogen and oxygen evolution reactions, causing the electrolyte to dry up, so electrolyte and water need to be continuously added to ensure the normal operation of the battery; 2) Acid gas overflow will corrode surrounding equipment, causing large economic losses and a certain degree of environmental pollution; 3) When the battery is in the discharged state, the active material of the negative plate is PbSO with smaller particles and larger specific surface area. 4 However, the size of these crystals will continue to grow as the reaction proceeds, and the solubility will decrease, resulting in serious sulfation, which will lead to a decrease in the cycle life of the lead-acid battery. Therefore, how to modify the negative electrode of the lead-acid battery in view of the above shortcomings has become a research hotspot.

[0003] In lead-acid batteries, in order to improve the conductivity, charge acceptance and cycle life of the negative active material of the lead-acid battery, carbon materials (such as carbon black, activated carbon, graphite, carbon fiber, graphene) are often added to the negative plate. The hydrogen evolution overpotential of these carbon materials is relatively low, which will lead to excessive hydrogen evolution rate in the negative plate. Excessive hydrogen evolution rate will cause serious water loss in the battery and increase in internal pressure of the battery. Therefore, it is necessary to develop a negative electrode additive and introduce it into the negative plate, which can not only effectively improve the sulfation phenomenon in the negative plate, but also reduce the occurrence of hydrogen evolution reaction, and improve the cycle life and hydrogen evolution overpotential of the lead-acid battery. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a negative electrode additive for a lead-acid battery and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A negative electrode additive for a lead-acid battery, the negative electrode additive being SnO 2 A composite material prepared by combining SnO 2@COF@ porous carbon nitride nanotubes, where the amount of negative electrode additive added is 0.25% of the mass of lead powder in the negative electrode of the lead-acid battery;

[0007] A method for preparing a negative electrode additive for a lead-acid battery comprises the following steps:

[0008] Step A1, adding melamine to deionized water, and then placing it in an 85°C oil bath and stirring for 10-20 minutes, then adding phenylphosphoric acid and continuing to stir for 1 hour, then transferring the obtained mixed solution to a reactor, reacting at 180°C for 8-12 hours, filtering and drying after the reaction, and then placing the obtained product in a muffle furnace and heating it to 520°C and maintaining it for 2 hours to obtain porous carbon nitride nanotubes;

[0009] Step A2, disperse the porous carbon nitride nanotubes in dimethyl sulfoxide and mix them evenly, then add [1,1'-biphenyl]-3,3',5,5'-tetraamine and terephthalaldehyde and mix them evenly, then dropwise add acetic acid solution under stirring conditions, and stir at room temperature for 10-30 minutes. After the reaction is completed, wash and dry to obtain COF@porous carbon nitride nanotubes;

[0010] Step A3, adding tin salt to deionized water and stirring evenly, adjusting the pH to 5-7, then adding COF@porous carbon nitride nanotubes and stirring for 40-60 minutes, filtering, washing, and drying, and then calcining the obtained precursor at 600-800° C. for 2-3 hours. After the reaction is completed, a negative electrode additive for lead-acid batteries is obtained;

[0011] Furthermore, in step A1, the mass ratio of melamine, phenylphosphoric acid and deionized water is 1:0.06-0.1:80;

[0012] Further, in step A1, the heating rate of the muffle furnace is 2-4°C / min;

[0013] Further, in step A2, the amount ratio of porous carbon nitride nanotubes, dimethyl sulfoxide, [1,1'-biphenyl]-3,3',5,5'-tetraamine, terephthalaldehyde and acetic acid solution is 0.1-0.5 g: 50 mL: 0.06-0.12 g: 0.03-0.06 g: 15-20 mL;

[0014] Further, the concentration of the acetic acid solution in step A2 is 10-15 mol / L;

[0015] Further, the tin salt in step A3 is one or more of tin nitrate, tin sulfate and tin chloride;

[0016] Furthermore, in step A3, the usage ratio of tin salt, deionized water and COF@porous carbon nitride nanotubes is 0.005-0.02 mol:100 mL:1 g.

[0017] Beneficial effects of the present invention:

[0018] The negative electrode additive prepared by the present invention is SnO 2 @COF@ porous carbon nitride nanotubes, the addition of this negative electrode additive effectively improves the sulfation phenomenon of the negative electrode of the lead-acid battery, improves the high-rate partial charge state of the lead-acid battery, and thus improves the cycle life of the battery. At the same time, it also increases the hydrogen evolution overpotential of the negative electrode plate and reduces the hydrogen evolution, which can effectively alleviate the water loss of the electrolyte, the increase in internal pressure of the battery and the impact on the electrode plate, which is beneficial to maintain the stability of the electrode plate and the battery, thereby improving the battery performance.

[0019] SnO 2 @COF@ porous carbon nitride nanotubes, firstly, melamine and phenylphosphoric acid are used as raw materials to synthesize porous carbon nitride nanotubes; then [1,1'-biphenyl]-3,3',5,5'-tetraamine and terephthalaldehyde are used as monomers for synthesizing COF, COF is synthesized on the surface of carbon nitride nanotubes to obtain COF@ porous carbon nitride nanotubes; then, tin salt is used as raw material to load tin dioxide on the surface of COF@ porous carbon nitride nanotubes to obtain SnO 2 @COF@Porous carbon nitride nanotubes. This negative electrode additive has excellent conductivity. After adding it to the negative electrode, it can form a conductive network inside the plate, improve the electron migration rate, and increase the utilization rate of the negative electrode active material (NAM), thereby promoting PbSO 4 reduction; in addition, the additive can also increase the porosity of the negative electrode active material, allowing the electrolyte to diffuse on the surface and inside of the negative electrode active material, thereby promoting the reaction rate; during the formation process of COF in the additive, the amino groups on the surface of the nanotubes are used to make the two tightly combined, forming a mesoporous structure at the junction of the two, and at the same time increasing the specific surface area of ​​the additive, thereby increasing the reaction interface, which is PbSO 4 Providing more sites to slow down PbSO 4The porous structure can inhibit the growth of lead sulfate dendrites and sulfation, thereby improving the cycle life of lead-acid batteries. At the same time, the porous structure can provide a channel for the electrolyte to be transported to the inside of the electrode plate, thereby improving the contact between the electrolyte and NAM and improving the battery performance. The introduction of N element has a good effect on inhibiting hydrogen evolution, which can effectively inhibit the problem of accelerated hydrogen evolution rate caused by the low hydrogen evolution overpotential of carbon materials, thereby reducing the problem of excessive water loss and increased internal pressure of the battery caused by excessive hydrogen evolution. In addition, the loading of tin dioxide can also reduce the precipitation of hydrogen. This is because tin dioxide will be converted into tin sulfate during the reaction, and the introduction of tin atoms increases the hydrogen evolution overpotential of the negative plate, reducing the precipitation of hydrogen, thereby effectively alleviating the loss of water in the electrolyte, the increase in internal pressure of the battery and the impact on the electrode plate, which is conducive to maintaining the stability of the electrode plate and the battery, thereby improving the performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 This is an electron microscope image of porous carbon nitride nanotubes.

[0022] Figure 2 This is an electron microscope image of COF@porous carbon nitride nanotubes.

[0023] Figure 3 This is the pore size distribution diagram of COF@porous carbon nitride nanotubes.

[0024] Figure 4 This is an electron microscope image of the surface of the negative electrode additive.

[0025] Figure 5 It is the cycle life diagram of Examples 4-6 and Comparative Examples 1-3. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0027] A method for preparing a negative electrode additive for a lead-acid battery comprises the following steps:

[0028] Step A1, add 1g of melamine to 80g of deionized water, then place it in an 85°C oil bath and stir for 10min, then add 0.06g of phenylphosphoric acid and continue stirring for 1h, then transfer the obtained mixed solution to a reactor, react at 180°C for 8h, filter and dry after the reaction, then place the obtained product in a muffle furnace, and heat it to 520°C at a heating rate of 2°C / min, and keep it for 2h to obtain porous carbon nitride nanotubes;

[0029] Step A2, 0.1 g of porous carbon nitride nanotubes were dispersed in 50 mL of dimethyl sulfoxide and mixed evenly, and then 0.06 g of [1,1'-biphenyl]-3,3',5,5'-tetraamine and 0.03 g of terephthalaldehyde were added and mixed evenly, and then 15 mL of 15 mol / L acetic acid solution was added dropwise under stirring conditions, and stirred at room temperature for 10 min. After the reaction was completed, the mixture was washed and dried to obtain COF@porous carbon nitride nanotubes;

[0030] Step A3, add 0.005 mol of tin chloride to 100 mL of deionized water and stir evenly, and adjust the pH to 7, then add 1 g of COF@porous carbon nitride nanotubes and stir for 40 min, filter, wash, and dry, and then calcine the obtained precursor at 600 ° C for 2 h. After the reaction is completed, the negative electrode additive for lead-acid batteries is obtained. Example 2

[0031] A method for preparing a negative electrode additive for a lead-acid battery comprises the following steps:

[0032] Step A1, add 1g of melamine to 80g of deionized water, then place it in an 85°C oil bath and stir for 15min, then add 0.08g of phenylphosphoric acid and continue stirring for 1h, then transfer the obtained mixed solution to a reactor, react at 180°C for 10h, filter and dry after the reaction, then place the obtained product in a muffle furnace, and heat it to 520°C at a heating rate of 3°C / min, and keep it for 2h to obtain porous carbon nitride nanotubes;

[0033] Step A2, 0.3 g of porous carbon nitride nanotubes were dispersed in 50 mL of dimethyl sulfoxide and mixed evenly, and then 0.09 g of [1,1'-biphenyl]-3,3',5,5'-tetraamine and 0.045 g of terephthalaldehyde were added and mixed evenly, and then 18 mL of 12 mol / L acetic acid solution was added dropwise under stirring conditions, and stirred at room temperature for 20 min. After the reaction was completed, the mixture was washed and dried to obtain COF@porous carbon nitride nanotubes;

[0034] Step A3, add 0.01 mol of tin chloride to 100 mL of deionized water and stir evenly, and adjust the pH to 6, then add 1 g of COF@porous carbon nitride nanotubes and stir for 50 min, filter, wash, and dry, and then calcine the obtained precursor at 700 ° C for 2.5 h. After the reaction is completed, the negative electrode additive for lead-acid batteries is obtained. Example 3

[0035] A method for preparing a negative electrode additive for a lead-acid battery comprises the following steps:

[0036] Step A1, adding 1g of melamine to 80g of deionized water, and then placing it in an 85°C oil bath and stirring for 20min, then adding 0.1g of phenylphosphoric acid and continuing to stir for 1h, then transferring the obtained mixed solution to a reactor, reacting at 180°C for 12h, filtering and drying after the reaction, and then placing the obtained product in a muffle furnace, and heating it to 520°C at a heating rate of 2°C / min, and maintaining it for 2h, to obtain porous carbon nitride nanotubes;

[0037] Step A2, 0.5 g of porous carbon nitride nanotubes were dispersed in 50 mL of dimethyl sulfoxide and mixed evenly, and then 0.12 g of [1,1'-biphenyl]-3,3',5,5'-tetraamine and 0.06 g of terephthalaldehyde were added and mixed evenly, and then 20 mL of 10 mol / L acetic acid solution was added dropwise under stirring conditions, and stirred at room temperature for 30 min. After the reaction was completed, the mixture was washed and dried to obtain COF@porous carbon nitride nanotubes;

[0038] Step A3, add 0.02 mol of tin chloride to 100 mL of deionized water and stir evenly, and adjust the pH to 5, then add 1 g of COF@porous carbon nitride nanotubes and stir for 60 min, filter, wash, and dry, and then calcine the obtained precursor at 800 ° C for 3 h. After the reaction is completed, the negative electrode additive for lead-acid batteries is obtained. Example 4

[0039] Preparation of negative electrode plate: all raw materials of negative electrode lead paste are put into a small paste mixing machine and dry mixed for 30 minutes, the mixed lead paste is coated on the negative electrode grid, and the wet plate is cured to obtain the negative electrode plate. The formula of negative electrode paste is 0.5% barium sulfate, 0.5% sodium sulfate, 0.05% humic acid, 0.05% lignin, 0.02% polyester staple fiber, negative electrode additive for lead-acid battery prepared in Example 1, 12% pure water and the balance of lead powder, wherein the negative electrode additive for lead-acid battery accounts for 0.25% of the mass of lead powder.

[0040] Preparation of positive electrode plate: Put all the raw materials of positive lead paste into a small paste mixing machine and dry mix for 30 minutes, apply the mixed lead paste on the positive grid, and cure the wet plate to obtain the positive electrode plate. The positive electrode paste formula is 20% red lead, 15% sulfuric acid, 20% water, 0.02% polyester staple fiber, and the balance is lead powder.

[0041] The negative plate and the positive plate are assembled into a 12Ah 2V lead-acid battery, with glass fiber wool as the separator and a filling density of 1.325g / cm 3 The sulfuric acid aqueous solution is used as the electrolyte to internalize the battery and form a good lead-acid battery for the next test. Example 5

[0042] The negative electrode plate was prepared using the negative electrode additive for lead-acid batteries prepared in Example 2, wherein the negative electrode additive for lead-acid batteries accounted for 0.25% of the mass of the lead powder, and the remaining steps were the same as in Example 4. Example 6

[0043] The negative electrode plate was prepared by using the negative electrode additive for lead-acid batteries prepared in Example 3, wherein the negative electrode additive for lead-acid batteries accounted for 0.25% of the mass of the lead powder, and the remaining steps were the same as in Example 4.

[0044] Comparative Example 1

[0045] Compared with Example 6, the negative electrode plate is prepared by replacing the negative electrode additive for lead-acid batteries prepared in Example 3 with conductive carbon black, wherein the conductive carbon black accounts for 0.25% of the mass of the lead powder, and the remaining steps are the same as in Example 4.

[0046] Comparative Example 2

[0047] Compared with Example 6, COF@porous carbon nitride nanotubes are used instead of the negative electrode additive for lead-acid batteries prepared in Example 3 to prepare the negative electrode plate, wherein the COF@porous carbon nitride nanotubes account for 0.25% of the mass of the lead powder, and the remaining steps are the same as in Example 4.

[0048] Comparative Example 3

[0049] Compared with Example 6, the negative electrode plate is prepared by replacing the negative electrode additive for lead-acid batteries prepared in Example 3 with porous carbon nitride nanotubes, wherein the porous carbon nitride nanotubes account for 0.25% of the mass of the lead powder, and the remaining steps are the same as in Example 4.

[0050] The lead-acid batteries assembled in Examples 4-6 and Comparative Examples 1-3 were subjected to performance tests:

[0051] HRPSoC cycle performance test: In order to study the effect of additive materials on the high rate partial state of charge cycle life of lead-acid batteries, Examples 4-6 and Comparative Examples 1-3 were tested at 1C to obtain the high rate partial state of charge cycle life of the batteries. When the cut-off voltage was lower than 1.75V, the cycle was terminated.

[0052] Hydrogen evolution potential test: The electrochemical performance of the lead-acid electrode was tested using a WaveDriver electrochemical workstation, and the negative electrodes obtained in Examples 4-6 and Comparative Examples 1-3 were subjected to hydrogen evolution potential tests; the test results are shown in the following table:

[0053]

[0054] It can be seen from the above table that the lead-acid battery obtained by using the negative electrode additive prepared by the present invention has an HRPSoC cycle life in the range of 7792-7991 cycles after HRPSoC cycle performance test, indicating that the addition of the negative electrode additive can improve the sulfation problem of the negative electrode of the lead-acid battery and increase the high-rate partial charge state cycle life of the lead-acid battery; the hydrogen evolution point test found that the hydrogen evolution overpotential was 1.3-1.4v, indicating that the addition of the negative electrode additive can increase the hydrogen evolution overpotential of the negative electrode, reduce hydrogen precipitation, and improve the battery performance.

[0055] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A negative electrode additive for a lead-acid battery, characterized in that: The negative electrode additive is a composite material prepared by combining SnO2, COF and carbon nitride nanotubes, and the composite material is SnO2@COF@porous carbon nitride nanotubes, wherein the amount of the negative electrode additive added is 0.25% of the mass of the negative electrode lead powder of the lead-acid battery; The method for preparing the negative electrode additive for lead-acid batteries comprises the following steps: Step A1, adding melamine to deionized water, and then placing it in an 85°C oil bath and stirring for 10-20 minutes, then adding phenylphosphoric acid and continuing to stir for 1 hour, then transferring the obtained mixed solution to a reactor, reacting at 180°C for 8-12 hours, filtering and drying after the reaction, and then placing the obtained product in a muffle furnace and heating it to 520°C and maintaining it for 2 hours to obtain porous carbon nitride nanotubes; Step A2, disperse the porous carbon nitride nanotubes in dimethyl sulfoxide and mix them evenly, then add [1,1'-biphenyl]-3,3',5,5'-tetraamine and terephthalaldehyde and mix them evenly, then dropwise add acetic acid solution under stirring conditions, and stir at room temperature for 10-30 minutes. After the reaction is completed, wash and dry to obtain COF@porous carbon nitride nanotubes; Step A3, add tin salt to deionized water and stir evenly, and adjust the pH to 5-7, then add COF@porous carbon nitride nanotubes and stir for 40-60 minutes, filter, wash, and dry, and then calcine the obtained precursor at 600-800°C for 2-3 hours. After the reaction is completed, the negative electrode additive for lead-acid batteries is obtained.

2. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: In step A1, the mass ratio of melamine, phenylphosphoric acid and deionized water is 1:0.06-0.1:

80.

3. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: The heating rate of the muffle furnace in step A1 is 2-4°C / min.

4. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: In step A2, the usage ratio of porous carbon nitride nanotubes, dimethyl sulfoxide, [1,1'-biphenyl]-3,3',5,5'-tetraamine, terephthalaldehyde and acetic acid solution is 0.1-0.5 g: 50 mL: 0.06-0.12 g: 0.03-0.06 g: 15-20 mL.

5. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: The concentration of the acetic acid solution in step A2 is 10-15 mol / L.

6. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: The tin salt in step A3 is one or more of tin nitrate, tin sulfate and tin chloride.

7. A negative electrode additive for lead-acid batteries according to claim 1, characterized in that: In step A3, the dosage ratio of tin salt, deionized water and COF@porous carbon nitride nanotubes is 0.005-0.02 mol:100 mL:1 g.

Citation Information

Patent Citations

  • Electrode active material for lead-acid storage battery

    CN106876666A

  • Porous carbon-loaded ultra-small SnO2 nanoparticle composite material and preparation method and application thereof

    CN111453765A